Meningkatkan Kualitas Pembelajaran Guru Dengan Mengefektifkan Supervisi Kelas Berbasis Klinis Melalui Pendekatan PIS di SDN Sindanglaya 2 - Triharto Triharto (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
This reasearch aims to improve the quality of teacher learning by effectivitying clinical based classroom supervision at SDN Sindanglaya 2 and trying to investigate the obstacles encountered in the implementation of the clinical-based classroom supervision in order to improve the quality of teacher learning. This reasearch uses a study design school action with 2 cycles. Each cycle consists of phases of planning, action, observation and reflection. The subjects of this study are 8 teachers at SDN Sindanglaya 2. The research instrument used is the instrument of clinical supervision, evaluation sheets and lesson plan implementation assessment of learning sheets. The result of this reasearch concluded that (1) the clinical based classroom supervision can improve the learning quality of teachers at SDN Sindanglaya 2. Based on the assestment results of lesson plan is an average of 3.4 in the first cycle and 4.4 in the second cycle, and the results of the implementation of learning management assestment an average of 3.7 in the first cycle and 4.3 in the second cycle (2) the problem faced in the implementation of the clinical-based classroom supervision is not all teachers are ready for clinical supervised.